ChemInform Abstract: Sulfur—Selenium Isomorphous Substitution in the AgAu(S, Se) Series. Issue 17 (April 2016) - Palyanova, Galina A.; Seryotkin, Yurii V.; Bakakin, Vladimir V.; Kokh, Konstantin A.
Abstract: AgAuS1‐x Sex (x = 0, 0.25, 0.5, 0.75, 1) phases are prepared by solid state reaction of the elements (1050 °C, 12 h) and subsequent annealing (150—500 °C, 3—30 d).